Women’s Autonomy and Tradition in Making Decision on Place of Delivery and Birth Attendants - Annisa Nurrachmawati; Anna Marie Wattie; Mohammad Hakimi; Adi Utarini (Jurnal Kesehatan Masyarakat Andalas, 2018)
Data from the Basic Health Research survey (Riskesdas) in 2013 showed that 33.3% deliveries in Indonesia occurred outside health facilities. Culture and gender influenced the decision-making process regarding place of delivery and birth attendants. A qualitative longitudinal study with an ethnography study design was conducted to explore the socio-cultural context and women’s autonomy in the dynamics of decision making regarding  place of delivery and birth attendants. This study was conducted in the working area of Muara Kaman Health Center, Kutai Kertanegara, East Kalimantan. In-depth interviews with 17 pregnant women were conducted since the first or second trimester of pregnancy until childbirth. Data were analyzed using thematic analysis. Nine informants delivered at the health facilityand eight informants chose home delivery.Those who delivered at the health facility made their own decision. Nevertheless some informants who were autonomous still chose homebirth, either assisted by  midwives, TBAs, or both. Women whose choice was decided by others (husbands, parents and TBAs), all gave birth at home assisted by TBAs. Women’s autonomy needs to be strengthened by improved knowledge, practice of delivery plan and also increase family support to enable women to choose health facilities as place for delivery.